Penguatan Inovasi Masyarakat melalui Program Innovation Camp and Competition STIA LAN Bandung - Siregar, Izza Nur Lathifa; Yulianti, Nadia; Mursalim, Siti Widharetno (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This study aims to analyze the impact of the Innovation Camp and Competition program on strengthening community innovation. It explores how this program fosters creativity, problem-solving skills, and local economic development through collaborative innovation initiatives. Methodology: This research employs a qualitative approach with a case study method, conducted in various local communities implementing the Innovation Camp and Competition program. Data were collected through in-depth interviews with program participants and organizers, direct observations during program implementation, and document analysis of innovation outcomes. Thematic analysis was performed using (Braun & Clarke, 2023) framework to identify key patterns and themes. Results: The findings indicate that the Innovation Camp and Competition program significantly enhances participants’ ability to generate creative solutions to local challenges. The program fosters an innovative mindset, strengthens community collaboration, and contributes to sustainable economic activities. Key success factors include government support, private sector involvement, and active community participation. Conclusion: Training in Central Lampung effectively improved conflict mapping skills, with increased scores and calls for more practical sessions and sustained support. Limitations: This study focuses on specific case studies, limiting the generalizability of findings. Further research with broader coverage and comparative analysis across different regions is recommended. Contribution: This study contributes to the field of community development, social innovation, and entrepreneurship education. It provides insights for policymakers, educators, and program developers on designing effective innovation-driven community empowerment program.